2018
DOI: 10.1007/s00265-018-2534-2
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in life history, behavior, and physiology along a slow-fast continuum: a meta-analysis

Abstract: The pace-of-life syndrome (POLS) hypothesis predicts that behavior and physiology covary with life history. Evidence for such covariation is contradictory, possibly because systematic sources of variation (e.g. sex) have been neglected. Sexes often experience different selection pressures leading to sex-specific allocation between reproduction and self-maintenance, facilitating divergence in life-history. Sex-specific differences in means and possibly variances may therefore play a key role in the POLS framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
88
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 106 publications
(166 reference statements)
2
88
0
Order By: Relevance
“…Yet, in congruence with the results of a recent meta‐analysis (Tarka et al. ), we did not find any effects of sex on any of the examined traits. However, we note that the trait that we found to be correlated with life‐history was aggression, a trait that is rather sex‐specific in killifishes.…”
Section: Discussionsupporting
confidence: 92%
“…Yet, in congruence with the results of a recent meta‐analysis (Tarka et al. ), we did not find any effects of sex on any of the examined traits. However, we note that the trait that we found to be correlated with life‐history was aggression, a trait that is rather sex‐specific in killifishes.…”
Section: Discussionsupporting
confidence: 92%
“…gradients of risks and resources) in their models and tests of POLS (Montiglio et al 2018, topical collection on Pace-of-life syndromes; Salzman et al 2018, topical collection on Pace-of-life syndromes; Tieleman 2018, topical collection on Pace-of-life syndromes); (3) given the fundamental differences in life history between males and females, aspects of POLS should be sex-specific , topical collection on Pace-of-life syndromes; Immonen et al 2018, topical collection on Pace-of-life syndromes; Lehmann et al 2018, topical collection on Pace-of-life syndromes; Tarka et al 2018, topical collection on Pace-of-life syndromes); (4) POLS can be studied at different levels of variation, but "raw" phenotypic correlations between POLS traits (the prevailing level at which data are currently analysed: Royauté et al 2018, topical collection on Pace-of-life syndromes) alone seem relatively uninformative; (5) empirical studies should test the fundamental assumptions first (i.e. the trade-offs between life-history traits indicative of current versus future reproduction), use relevant traits (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing and evaluating the current knowledge on the genetic basis of POLS-traits and their covariation, they discuss how a sex-specific genetic architecture might evolve and how hormonal and metabolic mechanisms might mediate sex differences proximately. In a meta-analysis of empirical studies, Tarka et al (2018), topical collection on Pace-of-life syndromes found no general support for sex differences in mean and variances for POLS-related traits, but males tended to have a faster life history, particularly under wild conditions and in species with polygynous mating systems. Using data from a contemporary human population, Lehmann et al (2018), topical collection on Pace-of-life syndromes showed that POLS relationships were similar for boys and girls, but that the sexes differed in the strength of trait associations.…”
Section: Contributions To and Insights From The Topical Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptive theory predicts that aggressive, bold or explorative individuals trade‐off future for current reproduction, leading to a faster pace‐of‐life (Dammhahn et al, ; Mathot & Frankenhuis, ; Réale et al, ). Previous tests utilizing life span as a proxy for allocation to future reproduction failed to overall support pace‐of‐life syndrome (POLS) theory (meta‐analyses: Royaute et al, ; Tarka, Guenther, Niemelä, Nakagawa, & Noble, ). We identified here within‐individual patterns of age‐dependent reproduction, and potentially reproductive senescence, as key components of life history varying with individual risky behaviour.…”
Section: Discussionmentioning
confidence: 99%